Substantive Reasoning of Religious Court Judges in Granting Compulsory Will Rights to Non -Muslims - Agustiar Agus (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2024)
The main problem of this study is related to the concept of Wasiat Wajibah which is not yet known in classical fiqh and the absence of provisions in Indonesian law that can be used by judges in granting the right of Wasiat Wajibah to non-Muslims. This study aims to analyze the substantive reasoning used by Indonesian religious court judges in resolving complications that occur through judicial decisions. This research uses a content analysis approach. The data source used is Decision Number 263/ Pdt.G /2007/ PTA.Sby . The decision was analyzed using the content analysis method. The data used is secondary data consisting of primary legal materials in the form of Wasiat Wajibah decisions of the Indonesian Religious Courts, as well as secondary and tertiary legal materials. The data was analyzed using a qualitative normative analysis method. The results of this study indicate that the substantive reasoning used by the judge in his decision is first, consideration of the maslahah perspective to maintain the five elements of Sharia: protection of religion ( hifzu'd -din), protection of the soul ( hifz 'un -). nafs ), maintenance of reason ( hifz al- akl ), protection of wealth ( hifz-i mal), protection of offspring ( hifz-i nasl ).